Arabic Language for the Indonesian Migrant Workers in Arabic Countries - Ahmad Maghfurin (Zien Journals, 2023)
The Arabic language came to Indonesia at the same time as the arrival of Islamic teachings (Suryanegara, 1995). Like its entry, Arabic also spread together with the spread of Islam. Because it is directly related to religion, Arabic is the most widely studied foreign language by Indonesian people in formal and informal institutions. Formally, this language is studied by kindergarten to university students. Meanwhile, in informal institutions, Arabic is also studied in mosques, majlis ta'lim, and even in the family
Keywords: Arabic language; Islamic teachings